D’Gondangrejo Resto Investment Agreement: Legal Construction and Legal Protection for the Parties Involved - Ardio Ragamufti Wisanggeni; Kelik Wardiono (Dinasti Research, 2025)
This research is prompted by the rapid growth of investment in the culinary and recreation sectors within the strategic toll gate area of Gondangrejo, Karanganyar Regency, which has triggered various local investment cooperation models. A prominent phenomenon is the investment agreement at D’Gondangrejo Resto, involving fixed asset capital participation that often lacks specific regulation under named agreement categories. The purpose of this study is to dissect the legal construction underlying such cooperation and analyze the legal protection mechanisms for both investors and business owners to ensure legal certainty. The research method employed is normative legal research with a statutory approach and a conceptual approach, utilizing secondary data consisting of positive legal norms and relevant literature. The results indicate that the legal construction of the D’Gondangrejo Resto investment agreement is an innominate agreement which, substantially, can be analogized to a Limited Partnership (Commanditaire Vennootschap) based on Articles 19-21 of the Indonesian Commercial Code. In this structure, the investor serves as a limited partner (silent partner) responsible only for the capital invested, while the business owner acts as a general partner with full personal liability. Preventive legal protection is realized through clauses limiting liability and rights to financial transparency, while repressive legal protection is available through instruments of compensation and agreement cancellation pursuant to Article 1243 of the Civil Code in the event of a breach of contract (wanprestasi). The novelty of this research lies in its proposal of a commercial law analogy (de facto CV) to provide legal protection standards for micro-to-medium investments using hybrid contract schemes outside formal corporate entities. These findings offer a theoretical contribution to the development of local investment contract law and practical implications for strengthening cooperation agreements in the culinary service sector.